Character education development through bioprospecting of medicinal plants in Indonesian national park - Suhadi, Lilik Nurkholidah, Sri Endah Indriwati, (Opción, 2019)
The aim of the study is to investigate health behavior and character education development through bioprospecting of medicinal plants of citizen from Bromo Tengger Semeru National Park. The medicinal plants were determined by exploration methods in 6 sub-districts at there. Then, health behavior of citizens was determined by interviewing 20 respondents. The character building will solve the problems to save forests. This educational method emphasizes not only build personal soft skills, but also to keep local wisdom. As a result, it was bioprospects to integrate the character education into the education curriculum at every level of education in East Java